Cannabinoid Drugs-Related Neuroprotection as a Potential Therapeutic Tool Against Chemotherapy-Induced Cognitive Impairment - Boullon, Laura; Abalo, Raquel; Llorente-Berzal, Álvaro (Frontiers in Pharmacology, 2021)
In recent years, and particularly associated with the increase of cancer patients’ life expectancy, the occurrence of cancer treatment sequelae, including cognitive impairments, has received considerable attention. Chemotherapy-induced cognitive impairments (CICI) can be observed not only during pharmacological treatment of the disease but also long after cessation of this therapy. The lack of effective tools for its diagnosis together with the limited treatments currently available for alleviation of the side-effects induced by chemotherapeutic agents, demonstrates the need of a better understanding of the mechanisms underlying the pathology. This review focuses on the comprehensive appraisal of two main processes associated with the development of CICI: neuroinflammation and oxidative stress, and proposes the endogenous cannabinoid system (ECS) as a new therapeutic target against CICI. The neuroprotective role of the ECS, well described in other cognitive-related neuropathologies, seems to be able to reduce the activation of pro-inflammatory cytokines involved in the neuroinflammatory supraspinal processes underlying CICI. This review also provides evidence supporting the role of cannabinoid-based drugs in the modulation of oxidative stress processes that underpin cognitive impairments, and warrant the investigation of endocannabinoid components, still unknown, that may mediate the molecular mechanism behind this neuroprotective activity. Finally, this review points forward the urgent need of research focused on the understanding of CICI and the investigation of new therapeutic targets.